2015
DOI: 10.1080/10942912.2015.1055360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Classification of Several Monofloral Iranian Honeys Based on Physicochemical Properties and Antioxidant Activity

Abstract: The aim of this study was to characterize and classify 10 honey samples collected from different regions of Iran based on their physicochemical properties. Moisture, ash and hydroxymethylfurfural (HMF) content, pH, electrical conductivity, diastase activity, color and fructose to glucose ratio were determined. Phenolic and flavonoid compounds, antioxidant activity and the ability to inhibit enzymatic browning were also evaluated in the samples. Based on diastase activity and hydroxymethylfurfural content, Tama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
(72 reference statements)
3
22
0
Order By: Relevance
“…Aazza et al [18] in a recent study on commercial Moroccan honeys, reported values of total phenol that are slightly greater than our results here; conversely our OR honey samples total phenol values are greater than those reported by Aazza et al [18] For all our studied Moroccan honey samples, both the DPPH and the FRAP values were generally lower than literature data. [31,32] However, as reported in the literature, [31,32] the reducing power and radical-scavenging ability show a general variability according the botanical source of nectar. Significant correlation factors (negative) were also found by plotting the lightness values L* against DPPH (p < 0.01), L* against FRAP (p < 0.01) and L* versus total phenols (p < 0.001).…”
Section: Resultsmentioning
confidence: 87%
“…Aazza et al [18] in a recent study on commercial Moroccan honeys, reported values of total phenol that are slightly greater than our results here; conversely our OR honey samples total phenol values are greater than those reported by Aazza et al [18] For all our studied Moroccan honey samples, both the DPPH and the FRAP values were generally lower than literature data. [31,32] However, as reported in the literature, [31,32] the reducing power and radical-scavenging ability show a general variability according the botanical source of nectar. Significant correlation factors (negative) were also found by plotting the lightness values L* against DPPH (p < 0.01), L* against FRAP (p < 0.01) and L* versus total phenols (p < 0.001).…”
Section: Resultsmentioning
confidence: 87%
“…[13] In recent years, improvement in the determination of botanical and geographical origins of honey was approached using multivariate analysis which is also known as the pattern recognition methods via principal component analysis (PCA), discriminant analysis (DA) and cluster analysis (CA). [17][18][19][20][21][22] However, work on determination of honey entomological origin is limited except for Duarte et al [8] who classified honeys into the bee species of Apis mellifera, Melipona spp., and Plebeia spp. using physiochemical and antioxidant properties, Silva et al [23] who classified honey into Apis mellifera and Melipona spp.…”
Section: Introductionmentioning
confidence: 99%
“…For the control sample, 2 mL of water was mixed with 2 mL solution of DPPH. [22] The percent inhibition was calculated using the following formula: %Inhibition ¼ control absorbance À sample absorbance ð Þ control absorbance  100 (1)…”
Section: Total Flavonoid Contentmentioning
confidence: 99%